Implementasi Media Digital Endorsement Buku Antologi #TeacherSquad Menggunakan Metode Multimedia Development Life Cycle - Ely Purnawati (Media Aplikom, 2021)
The existence of a book becomes important in human life. The book "#TeacherSquad: Salam dari Negeri Kiwi" is an anthology book containing a collection of short stories created by alumni who got the 2017 Ministry of Education and Culture's flagship scholarship program at Auckland University of Technology, New Zealand. But unfortunately there are still few people who know of its existence. In fact, this book has received appreciation from a number of figures including artists in Indonesia. Unfortunately, the endorser's statement is contained in the book so that it cannot be accessed by many people. The purpose of this research is to implement digital media in the endorsement of the anthology book #TeacherSquad. The method used is MDLC. In this research, a digital media endorsement for the anthology book #TeacherSquad was successfully implemented in the form of a video. This digital media has the essence of content compatibility and this media is worthy of use to help increase the endorsement of this book.